The effect of knowledge management on the performance of lecturers and performance of private universities - Umi Rusilowati; Denok Sunarsi; Azhar Affandi (Jurnal Konseling dan Pendidikan)
The purpose of this study is to analyze the relationship between  knowledge management on  lecturer performance,  knowledge management on private university performance, and lecturer performance on private university performance. This research is an explanatory research with a quantitative approach. The research was conducted at a private university in Tangerang City. A sample of 120 respondents with data collection using an online questionnaire which was analyzed using Structural Equation Modeling using the Smart PLS 3.0 data processing tool. The selection of the sample of respondents used simple random sampling. Based on the results of data processing, it is  concluded   that there is a significant influence of managerial knowledge on the performance of lecturers, a significant influence of managerial knowledge on lecturers' performance. The performance of private universities,  there is a significant influence of lecturer performance on the performance of private universities.